Level of Knowledge of Clean and Healthy Living Behavior and Screening of Dental Maloclusion to Enhance Quality of Life Related to Dental and Oral Health In Medowo I and II Elementary School Students - Rahmawati, Dwi; Ardani, I Gusti Wahju Aju; Nugraha, Alexander Patera (Indonesian Journal of Dental Medicine, 2022)
Background: The elementary school period is a golden age for instilling the values of clean and healthy living behaviour (CHLB) and has the potential as an agent of change to promote CHLB in schools, families and communities so as to create quality human resources in the future. Currently children are very vulnerable to dental and oral health, because at that age there is a transition or change of teeth, namely from deciduous teeth to permanent teeth, for that special attention needs to be given to dental and oral health so that the growth and development of teeth can be maintained properly. Purpose: to enhance knowledge of CHLB and screening of dental malocclusion in an effort to improve the quality of life related to dental and oral health. Methods: 116 participants from grades 3-5 elementary school students. Data was collected by means of intraoral examination and filling out pre-test and post-tests questionnaires. Furthermore, an analysis of the frequency distribution data was carried out by mean of statistical analysis. Results: male students had higher caries (59 people) and those who were not caries (4 people), compared to girls (47 people) and those who were not caries (6 people). CHLB knowledge level is good (86.8%), moderate (8.2) low (5%). Conclusion: caries in boys is higher than in girls and all respondents' knowledge of CHLB is good.